Role of anterior thalamic circuitry during sleep - Szabó, Johanna Petra; Fabó, Dániel; Pető, Nóra; Sákovics, Anna; Bódizs, Róbert (Epilepsy research, 2022)
Increased attention has been paid to the structure and function of anterior nucleus of the thalamus (ANT), since deep brain stimulation (DBS) treatment for epilepsy launched a decade ago. The efficacy of the treatment on seizure count varies patient from patient and we have limited information on the predictors of better outcomes. While the thalamus is considered the key brain region responsible for maintaining sleep, ANT was traditionally not involved in this function. Recent experimental and human data point to a possible role of ANT in sleep processes, although the underlying mechanisms are still ambiguous. Beside evaluating the current knowledge on sleep disturbances experienced during ANT-DBS treatment, the search for valid biomarkers primarily resides on a better understanding of sleep circuits implicating ANT and its subnuclei. Hypothetically better selectivity within the target may increase seizure outcomes and reduce psychiatric and cognitive side effects. Hence, the main scope of this review is to summarize the evidence on the activity measured in the ANT during non-REM and REM sleep. Furthermore, we aim to find shared properties of sleep processes and ANT-related functions examined more thoroughly during wakefulness, such as selective attention and memory. •summarize recent and historic knowledge gained form experimental and human thalamic recordings in sleep.•compare other thalamic structures with the anterior nucleus of thalamus (ANT).•review literature data in relevance of ANT subnuclei in sleep, attention and memory processes.•try to conclude on DBS targeting to increase anti epileptic efficacy and decease psychiatric and cognitive side effects.